2009
DOI: 10.1002/chem.200802499
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective SE2′ Protonation of α‐Hydroxyallylsilanes Mediated by a Brook Rearrangement

Abstract: Brooked up! Treatment of (R,Z)-3-(tert-butyldimethylsilyl)-1-cyano-3-hydroxyprop-1-enyl carbamate with a catalytic amount of a base afforded (S,E)-3-(tert-butyldimethylsilyloxy)-1-cyanoallyl diisopropylcarbamate, showing that S(E)2'-type reaction of allylsilicates proceeds in an anti fashion. The overall process is equivalent to trapping of an enantioenriched C-chiral carbanion at the alpha-position of nitrile group in up to 77 % ee (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A similar result was obtained with 4b to give (Z)-7. 9 It should be noted that both (E)-and (Z)-7 are products arising from a syn-attack ring-opening of the epoxide as shown in 4a′.…”
Section: Chirality Transfer From Epoxide To Carbanionmentioning
confidence: 98%
“…A similar result was obtained with 4b to give (Z)-7. 9 It should be noted that both (E)-and (Z)-7 are products arising from a syn-attack ring-opening of the epoxide as shown in 4a′.…”
Section: Chirality Transfer From Epoxide To Carbanionmentioning
confidence: 98%
“…We previously reported that the Brook rearrangement mediated S E 2 protonation of allylsilanes having an oxygen substituent on the stereogenic center proceeds in an anti fashion. [7] The synthesis of racemic siloxyallenes by a Brook rearrangement was originally reported independently by the Kuwajima [8] and Reich [9] groups. They generated a-hydroxypropargylsilane, a precursor for the Brook rearrangement, by reactions of acylsilanes with lithium acetylides.…”
mentioning
confidence: 99%